UTILIZATION OF E-COMMERCE, DIGITAL LITERACY AND ACCOUNTING INFORMATION SYSTEMS AS DRIVING FACTORS IN DECISION MAKING FOR ENTREPRENEURSHIP IN ACCOUNTING STUDENTS - Evi Rusdianti; Hadiah Fitriyah (Journal of Artificial Intelligence and Digital Economy, 2025)
Objective: This study aims to analyze the influence of e-commerce utilization, digital literacy, and accounting information systems on entrepreneurial decision-making among accounting students in Indonesia. The research emphasizes the role of technology in addressing unemployment challenges through entrepreneurship in developing countries like Indonesia. Method: A quantitative approach was employed with accounting students from the Muhammadiyah University of Sidoarjo, Class of 2021–2022, serving as respondents. Data were collected through questionnaires and analyzed using statistical methods to determine the effect of each variable on entrepreneurial decision-making. Results: The findings reveal that e-commerce has no significant impact on entrepreneurial decisions, while digital literacy and accounting information systems show a positive and significant influence on students’ entrepreneurial decision-making processes. Novelty: This study contributes to the growing body of knowledge on digital entrepreneurship in higher education by demonstrating that the integration of digital literacy and accounting information systems plays a more decisive role in fostering entrepreneurial behavior than e-commerce usage among accounting students in Indonesia.